Multiphysical Modeling of the Heating Phase in the Polymer Powder Bed Fusion Process - Siginer, D (Elsevier B.V., 2017)
A numerical framework based on a modified Monte Carlo ray-tracing method and the Discrete Element Method (DEM) is developed to predict the physical behavior of discrete particles during the Powder Bed Fusion (SLS) process. A comprehensive model coupling all major aspects of the underlying physics and the corresponding numerical framework, accounting for radiative heat transfer, heat conduction, sintering and granular dynamics among others, is developed. In particular, the effect of scattering on the laser-particle interaction is investigated and accounted for in the numerical framework. The spatially and temporally varying distribution of heat and displacement within the additively manufactured object are captured in detail. The model is validated through the comparison of simulated results with existing experimental results in the literature. © 2017 Elsevier B.V.